2012
DOI: 10.1037/a0027443
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural office design: A case example.

Abstract: The psychology and counseling literature contains numerous discussions of the need for psychotherapists to be culturally sensitive, including descriptions of the requisite skills and behaviors that affect the therapeutic alliance. In addition, a number of articles on diversity mention the need for multiculturally friendly offices and list some general guidelines. However, the literature contains no research, or even detailed guidelines, on the critical physical elements to consider in designing a multicultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 9 publications
2
16
0
2
Order By: Relevance
“…In the interviews, participants heavily emphasized this point: the relationship is the most important. The room is secondary to the relationship, similar to Benton and Overtree's (2012) previously mentioned claim that the room's importance follows directly behind the therapist. A poorly designed office or a meticulously designed room can evoke associations in clients that can support or inhibit the relationship.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the interviews, participants heavily emphasized this point: the relationship is the most important. The room is secondary to the relationship, similar to Benton and Overtree's (2012) previously mentioned claim that the room's importance follows directly behind the therapist. A poorly designed office or a meticulously designed room can evoke associations in clients that can support or inhibit the relationship.…”
Section: Discussionmentioning
confidence: 61%
“…Over the years, there has been an increasing number of studies linking the therapists’ office to therapeutic alliance (Backhaus, 2008; Bedi, 2006), and client behavior and feelings (Borenstein, 2006; Chaikin et al., 1976; Gutheil, 1992; Stanley et al., 2016). Benton and Overtree (2012) even argue that the physical environment “can determine whether or not a patient remains in therapy” (265). Similar claims are suggested by other researchers who have linked the office to first impressions of the quality of therapy (Devlin et al., 2009; Miwa and Hanyu, 2006; Nasar and Devlin, 2011) and to whether a client likes or dislikes their therapist (Sanders and Lehmann, 2019).…”
Section: The Psychotherapist’s Officementioning
confidence: 99%
“…Moreover we need to acknowledge that clients and clinicians are diverse and have different preferences. Benton and Overtree (2012) underline the need to design and decorate treatment units in non-excluding ways. They for example describe that decorations with an exclusively heterosexual orientation might make client in the LBGT community feel excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Some suggestions from the social work literature recommend including specific physical aspects such as a welcoming entry, availability of outdoor space, and a neutral doorway (Weeks, 2004) in social work offices. Authors from other fields have suggested that offices are more favorably viewed by clients when they display softness (Arneill & Devlin, 2002; Chaikin, Derlega, & Miller, 1976; Miwa & Hanyu, 2006; Nasar & Devlin, 2011), order (Devlin & Nasar, 2012; Nasar & Devlin, 2011), more than two credentials (Devlin et al, 2009), and have multicultural design when indicated (Benton & Overtree, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Benton and Overtree (2012) documented their renovations aimed at creating a multiculturally inclusive environment for their not-for-profit mental health clinic. Alterations were made based on information about their clientele, the community, and the professional literature.…”
Section: Literature Reviewmentioning
confidence: 99%